Abortion Conducted by Rape victims - Hermawan; Ahmad Syafi’i (Faculty of Law, Merdeka University Surabaya, 2018)
Law No. 36 of 2009 concerning Health states regulations that allow a person to have an abortion with two conditions, namely: indication of medical emergencies and pregnancy due to rape that can cause psychological trauma for rape victims. The highlight of the decriminalization of abortion is Article 75 of Law No. 36 of 2009 concerning Health, that basically abortion is prohibited, but there are exceptions, one of which is if the pregnancy is due to rape which can cause psychological trauma for rape victims.